2023
DOI: 10.18474/jes22-33
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Entomopathogenic Fungal-Based Insecticides against the Citrus Mealybug (Hemiptera: Pseudococcidae) on Coleus (Lamiales: Lamiaceae) Plants under Greenhouse Conditions1

Abstract: The citrus mealybug, Planococcus citri (Risso) (Hemiptera: Pseudococcidae), is an important insect pest of greenhouse-grown horticultural crops. Citrus mealybug causes direct plant damage when feeding on plant leaves, stems, flowers, and fruits, and this damage can result in substantial economic losses. Insecticides are used to manage citrus mealybug populations in greenhouse production systems. Although entomopathogenic fungal-based insecticides are labeled for use against citrus mealybug, there is no quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In conclusion, based on the findings of Herrick and Cloyd (2023) and the findings of the current study, entomopathogenic fungalbased insecticides alone or in mixtures with insect growth regulators are not effective in managing citrus mealybug populations on coleus plants. The temperature and relative humidity must be optimal for germination and infection to occur.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In conclusion, based on the findings of Herrick and Cloyd (2023) and the findings of the current study, entomopathogenic fungalbased insecticides alone or in mixtures with insect growth regulators are not effective in managing citrus mealybug populations on coleus plants. The temperature and relative humidity must be optimal for germination and infection to occur.…”
Section: Discussionmentioning
confidence: 58%
“…We found that the entomopathogenic fungalbased insecticides alone and in mixtures with the insect growth regulators tested were not effective in managing citrus mealybug populations on coleus plants under greenhouse conditions. The lack of efficacy may be attributed to the waxy covering protecting citrus mealybugs, which prevents the conidia of the entomopathogenic fungi from attaching to the cuticle (Herrick and Cloyd 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations